Prevalence and severity of depression in patients with the consequences of ischemic strokes and in patients with chronic brain ischemia - Babirad, A. (Journal of Education, Health and Sport, 2021)
The aim of our study was to investigate the prevalence and severity of depression in patients with the consequences of ischemic strokes and in patients with chronic brain ischemia. Material and Methods. We examined 100 patients with consequences of ischemic strokes and 17 patients with chronic cerebral ischemia. The Hamilton Depression Rating Scale was used to assess the presence and degree of depression. Conclusions. Slightly less than half of the patients with chronic cerebral ischemia (47.1%) had no depression, 42.1% had mild depression, and only 11.8% of the patients had moderate and severe depression. A different situation was observed in the group of patients with the consequences of ischemic strokes. Among them, only 22.0% of patients had no depression, 44.0% had mild depression, and 34.0% of patients had moderate, severe, and extremely severe depression (p < 0.05).